y = x – 13 when x = –3.
~
O 6N + 12N = 40
O 6N + 12 = 40
6(N + 12) = 40
Answer:
6(N + 12) = 40
Step-by-step explanation:
Number = N
Sum of a number and twelve:
N + 12
Six times the sum of a number and twelve:
6(N + 12)
Six times the sum of a number and twelve is forty:
6(N + 12) = 40
Answer:
6(N+12) = 40
Step-by-step explanation:
The statement says six times the sum . . .
From this we can tell that the answer will be 6 times two numbers added together. Those two numbers are "a number" (some variable) and 12.
We can tell that the variable is N, so it answer must be 6(N + 12) = 40